2021
DOI: 10.3390/math9192463
|View full text |Cite
|
Sign up to set email alerts
|

Stability Analysis and Optimization of Semi-Explicit Predictor–Corrector Methods

Abstract: The increasing complexity of advanced devices and systems increases the scale of mathematical models used in computer simulations. Multiparametric analysis and study on long-term time intervals of large-scale systems are computationally expensive. Therefore, efficient numerical methods are required to reduce time costs. Recently, semi-explicit and semi-implicit Adams–Bashforth–Moulton methods have been proposed, showing great computational efficiency in low-dimensional systems simulation. In this study, we exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…It should be noted that using the DF (PEC) methods requires twice the amount of memory compared to using ABM. However, these algorithms can be further optimized using the approach given in [17].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It should be noted that using the DF (PEC) methods requires twice the amount of memory compared to using ABM. However, these algorithms can be further optimized using the approach given in [17].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of computational efficiency, ref. [17] showed that semi-explicit and semiimplicit ABM methods are efficient methods compared to other linear multistep methods (such as ABM and BDF). Furthermore, it was shown in [17] that semi-explicit and semiimplicit ABM methods are sufficiently flexible to optimize the computations according to the problem features.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations